EDR Peptide: Possible Mechanism of Gene Expression and Protein Synthesis Regulation Involved in the Pathogenesis of Alzheimer’s Disease - Khavinson, Vladimir (Molecules, 2020)
The EDR peptide (Glu-Asp-Arg) has been previously established to possess neuroprotective properties. It activates gene expression and synthesis of proteins, involved in maintaining the neuronal functional activity, and reduces the intensity of their apoptosis in in vitro and in vivo studies. The EDR peptide interferes with the elimination of dendritic spines in neuronal cultures obtained from mice with Alzheimer’s (AD) and Huntington’s diseases. The tripeptide promotes the activation of the antioxidant enzyme synthesis in the culture of cerebellum neurons in rats. The EDR peptide normalizes behavioral responses in animal studies and improves memory issues in elderly patients. The purpose of this review is to analyze the molecular and genetics aspects of the EDR peptide effect on gene expression and synthesis of proteins involved in the pathogenesis of AD. The EDR peptide is assumed to enter cells and bind to histone proteins and/or ribonucleic acids. Thus, the EDR peptide can change the activity of the MAPK/ERK signaling pathway, the synthesis of proapoptotic proteins (caspase-3, p53), proteins of the antioxidant system (SOD2, GPX1), transcription factors PPARA, PPARG, serotonin, calmodulin. The abovementioned signaling pathway and proteins are the components of pathogenesis in AD. The EDR peptide can be AD.